Transgender Students’ Responses to Systemic Stressors in South African Universities - Buthelezi, Johannes; Brown, Anthony (International Journal of Humanities, Education, and Social Sciences, 2025)
This paper explores the retorts of students with transgender identities towards structural exclusion in institutions of higher learning. This cohort of student’s studies and reside in spaces that are suppressive, oppressive and marginalising for them. These and similar institutions of higher learning do not affirm inclusion and diverse gender diversity among student populations. For this reason, these transgender students are obligated to retort against these structural exclusions. This study is interested in finding out how students with transgender identities navigate through institutions of higher learning in pursuit of inclusivity. Eight participants who identify themselves as transgender students were sampled using a purposive sampling method. To comprehend their realities, a phenomenological approach is utilised through the adoption of an arts-based approach to collect data. Content data analysis is suitable to assess the reliability and validity of the raw data collected for this study. Furthermore, the minority stress theory (MST) underpins this study. The theory brings understanding of the impact of distal and proximal stressors caused by structural exclusions in the lives of students with transgender identities at institutions of higher learning. The findings of the study revealed that students with transgender expressions are excluded, discriminated and ‘othered’ because institutions of learning are characterised by direct and structural discrimination known as heterosexism. This article argues that the system is silent (or silencing) about the needs of students with transgender identities. These experiences create distal and proximal stressors that affect the well-being and academic work of transgender students. Therefore, radical transformation should be prioritised to ensure that institutions of learning are safe and inclusive spaces for all students.